Dynamic comparison on the technical efficiency between China's EPEs and PEs: Two-dimensional measurement based on SFA. (20th June 2023) - Wang, Ren; Duan, Yicheng
Abstract: It is of equal importance to improve the efficiency of environmental protection enterprises (EPEs) and polluting enterprises (PEs) for Environmental Protection and Green Development, which is a micro-foundation for China's economic transformation and high-quality development. This paper redefines the efficient frontier of enterprises, distinguishing between "absolute technical efficiency" (ATE) and "relative technical efficiency" (RTE), and conducts two-dimensional measurements and dynamic comparison to examine the technical efficiency characteristics of China's EPEs and PEs listed on the A-share market, based on the stochastic frontier analysis (SFA) method. The results demonstrate that, first, the ATE of EPEs exhibits a reverse upward trend, while the ATE of PEs and A-share enterprises as a whole is declining simultaneously. Second, in contrast to the shrinkage of the ATE and RTE of PEs, the efficient frontier of EPEs has experienced rapid expansion. Third, capital utilization efficiency, rather than economies of scale effects, appears to be the main obstacle impeding the technical efficiency performance of EPEs. Therefore, improving the capital utilization efficiency and the extent of coupling and coordination between capital and labor is the key to promoting the technical efficiency of EPEs. Fourth, targeted government subsidies and tax refunds for EPEs need to be improved and an external evaluation mechanism focusing on Environment, Social and Governance (ESG) rating needs to be strengthened. Consequently, it is essential to promote the combination of top-down targeted policy support and multi-dimensional external evaluation to guide capital flows and achieve their efficient utilization, which is also the basis of the environmental protection industry's high-quality development. Highlights: First, the ATE of EPEs exhibits a reverse upward trend, while the ATE of PEs is declining simultaneously. Second, in contrast to the shrinkage of the ATE and RTE of PEs, the efficient frontier of EPEs has experienced rapid expansion. Third, capital utilization efficiency is the main obstacle impeding the technical efficiency performance of EPEs. Fourth, targeted government subsidies and tax refunds for EPEs need to be improved and an external evaluation mechanism needs to be strengthened.